Characterization of patients with breast cancer and their accompaning relatives - María Elena Reina Suárez; Yamila Ramos Rangel; Leonor Cisnero Pimentel; María de los Ángeles Reina Sarmiento; Modesta Alcelú Sarduy; Miguel Ángel González Suárez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Introduction: breast cancer burst into the oncologic universeas one of the malignant tumors of higher presence worldwide which is really difficult to ignore. Objective: to characterize the patients diagnosed breast cancer and their relatives. Methods: descriptive study of all the patients with the dignosis of breast cancer, from May 2014 to December 2016 and their accompaning relatives at the Municipality of Rodas. The variables analyzed were: age, sex, schooling level, occupation, accompaning relative, evolution of the disease and treatment. Results: patients between 46 and 65 years old (72 %) predominated, with medium high schooling,(62 %) and with partnership relation. The number of ill women without employment was outstanding. The time of desease evolution showed the highest number of sick women from 3 to 5 years (50, 0 %), the prevailing oncospecific treatment was surgery and chemiotherapy (58,3 %). With respect to the accompaning relatives, a superiority of middleage adults predominated (62,5%) and women (72,2%). Higher level of schooling prevailed (50.0 %) and legal or consensual partnership relation (50,0 % and 29,2 % respectively), professionals (45,8 %) and technicians (25,0 %). Patients identified sons and daughters as the relative who accopany them in their disease process. Conclusions: breast cancer presented mainly of the fourth decade of life, in women with stable partner and generally with three to five years of evolution.